Nitrogen self-doped activated carbonsviathe direct activation ofSamanea samanleaves for high energy density supercapacitors - Vichuda Sattayarut; Thanthamrong Wanchaem; Pundita Ukkakimapan; Visittapong Yordsri; Paweena Dulyaseree; Mayuree Phonyiem; Michiko Obata; Masatsugu Fujishige; Kenji Takeuchi; Winadda Wongwiriyapan; Morinobu Endo (My University, 2019)
In this study, nitrogen self-doped activated carbons (ACs) obtained via the direct activation of Samanea saman green leaves (SSLs) for high energy density supercapacitors were investigated. The SSL-derived direct-activated carbons (hereinafter referred to SD-ACs) were synthesized by impregnating sodium hydroxide as an activating agent and heating up to 720 °C without a hydrothermal carbonization or pyrolysis step. The optimum condition was investigated by varying the weight ratio of raw SSLs to NaOH. Surpassing the ACs derived from the two-step convention method, SD-ACs showed superior properties, including a higher surface area (2930 m2 g-1), total pore volume (1.37 cm3 g-1) and nitrogen content (4.6 at%). Moreover, SD-ACs exhibited enhanced electrochemical properties with specific gravimetric and volumetric capacitances of 179 F g-1 and 88 F cm-3 in an organic electrolyte, respectively, a high capacitance retention of approximately 87% at a current density of 0.5 A g-1 and excellent cycling stability of 97.5% after 3000 cycles at a current density of 5 A g-1. Moreover, the potential window of the supercapacitor cell was extended to 3.5 V with a significantly enhanced energy density of up to 79 W h kg-1. These results demonstrate that the direct activation of nitrogen-enriched SSLs offers advantages in terms of simplicity, low-cost and sustainable synthetic route to achieve nitrogen self-doped ACs for high energy density supercapacitors, which exhibit superior properties to that of ACs prepared via the conventional method.
Keywords: Supercapacitor Materials and Fabrication